Assessment of Probability of Pulmonary Fibrosis Progression in Patients with Interstitial Lung Diseases to Determine Further Treatment Tactics - A. A. Lukashevich; O. A. Yudina; L. S. Bogush; E. I. Davidovskaya; M. I. Dyusmikeeva; A. F. Belko (Туберкулез и болезни лёгких)
The objective: to develop a method for assessing the probability of progression of pulmonary fibrosis in patients with interstitial lung diseases in order to determine further treatment tactics.Subjects and Methods. 80 patients with interstitial lung diseases underwent lung biopsies with consequent morphological and immunohistochemical tests. The group with progressive fibrosis consisted of 42 patients. The prognostic model was built using the binary logistic regression method.Results. A statistical model was developed in the form of a regression equation consisting of 3 parameters: the presence of a morphological pattern of interstitial fibrosis; intensity of CTGF expression; and intensity of TGF-β expression. This mathematical model makes it possible to predict the progression of pulmonary fibrosis in patients with interstitial lung diseases with 83.3% sensitivity and 84.2% specificity.